The Hot Limit of Solar-like Oscillations From Kepler Photometry - Balona, Luis A. (Frontiers in Astronomy and Space Sciences, 2020)
Kepler short-cadence photometry of 2,347 stars with effective temperatures in the range 6,000–10,000 K was used to search for the presence of solar-like oscillations. The aim is to establish the location of the hot end of the stochastic convective excitation mechanism and to what extent it may overlap the δ Scuti/γ Doradus instability region. A simple but effective autocorrelation method is described which is capable of detecting low-amplitude solar-like oscillations, but with significant risk of a false detection. The location of the frequency of maximum oscillation power, νmax, and the large frequency separation, Δν, is determined for 167 stars hotter than 6,000 K, of which 70 are new detections. Results indicate that the hot edge of excitation of solar-like oscillations does not appear to extend into the δ Scuti/γ Doradus instability strip.